Decoding atypical laryngeal growths – A case report - Dutta, Meghna; Ghosh, Abhik; Chatterjee, Suddhasatwya; Khan, Enam Murshed (Eastern Journal of Medical Sciences, 2022)
Respiratory papillomatosis is a relatively rare disease with a potential for devastating consequences. The viral etiology of this condition has been well established. Most often, the wart is successfully managed surgically. Post surgical removal, there exists a high chance of recurrence of the papilloma. It has been documented that surgical removal followed by an adjuvant therapy helps to delay the recurrence. Also, the use of quadrivalent human papillomavirus vaccine is expected to decrease the incidence of respiratory papillomatosis or help with treatment of the disease in the years to come. Here we discuss an unusually late presentation of adult-onset laryngeal papilloma that was managed with some deviation from the routine.